2020
DOI: 10.1371/journal.pone.0235703
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic limitations of clinical case definitions of pertussis in infants and children with severe lower respiratory tract infection

Abstract: Introduction Diagnosis of pertussis is challenging especially in infants. Most low and middle-income countries (LMIC) lack resources for laboratory confirmation, relying largely on clinical diagnosis alone for both case management and surveillance. This necessitates robust clinical case definitions. Objectives This study assesses the accuracy of clinical case definitions with and without lymphocytosis in diagnosing pertussis in children with severe lower respiratory tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In infants, clinical and biological evaluation evidenced that higher number of leukocytes, lymphocytes, platelets and cough duration were significantly associated to pertussis infection. While the relationship between platelets and pertussis is controversial, the association of white blood cell number and cough duration with pertussis was previously described in Iran and in other settings, including in HIC [ 19 , 20 ]. Of note, we observed that 62.5% of the confirmed positive infants coughed less than 14 days when seeking diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In infants, clinical and biological evaluation evidenced that higher number of leukocytes, lymphocytes, platelets and cough duration were significantly associated to pertussis infection. While the relationship between platelets and pertussis is controversial, the association of white blood cell number and cough duration with pertussis was previously described in Iran and in other settings, including in HIC [ 19 , 20 ]. Of note, we observed that 62.5% of the confirmed positive infants coughed less than 14 days when seeking diagnosis.…”
Section: Discussionmentioning
confidence: 99%